2019
DOI: 10.3765/salt.v29i0.4631
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneity or implicature: An experimental investigation of free choice

Abstract: A sentence containing disjunction in the scope of a possibility modal, such as Angie is allowed to buy the boat or the car, gives rise to the FREE CHOICE inference that Angie can freely choose between the two. This inference poses a well-known puzzle, in that it is not predicted by a standard treatment of modals and disjunction (e.g., Kamp 1974). To complicate things further, FREE CHOICE tends to disappear under negation: Angie is not allowed to buy the boat or the car doesn’t merely convey the negation of fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…There are also a variety of challenges for this approach stemming from certain differences between implicatures and free choice in their processing and acquisition profiles (Chemla and Bott 2014;Tieu et al 2016). Other challenges stem from the interaction between free choice and presuppositions (Romoli and Santorio 2019;Marty and Romoli 2019) and the status of positive versus negative sentences in certain contexts (Tieu et al 2018). 7 See Chierchia (2004Chierchia ( , 2013, Chierchia et al (2012), Magri (2009), Meyer (2013, among others.…”
Section: (19)mentioning
confidence: 99%
“…There are also a variety of challenges for this approach stemming from certain differences between implicatures and free choice in their processing and acquisition profiles (Chemla and Bott 2014;Tieu et al 2016). Other challenges stem from the interaction between free choice and presuppositions (Romoli and Santorio 2019;Marty and Romoli 2019) and the status of positive versus negative sentences in certain contexts (Tieu et al 2018). 7 See Chierchia (2004Chierchia ( , 2013, Chierchia et al (2012), Magri (2009), Meyer (2013, among others.…”
Section: (19)mentioning
confidence: 99%
“…This has at least two upshots. First, in the case of Free Choice Tieu et al 2019 found exactly the pattern of responses predicted by a homogeneity account. Second, Free Choice patterned quite differently than the early access Simon Goldstein kind of exclusivity implicature on display in (21-a).…”
Section: Early Accessmentioning
confidence: 53%
“…The pragmatic accounts in Chemla 2008 andFox 2007 differ from the accounts here in at least the treatment of Free Choice when disjunction takes wide scope to possibility modals and the treatment of duals to ♦ and ∨. In addition, we'll review recent experimental work in Santorio 2019 andTieu et al 2019 that seems to favor the present account. The semantic accounts in Aher 2012 and Aloni 2018 differ from our own by departing further from classical logic, giving up instances of the Law of Excluded Middle, Law of Non-Contradiction, and Explosion.…”
Section: Simon Goldsteinmentioning
confidence: 83%
See 2 more Smart Citations